The E-Patient - Ljubomir Kovachev; Pencho Tonchev; Kiril Nedialkov (Journal of Biomedical & Clinical Research)
Advanced information technologies have entered all spheres of human activities. In healthcare, this happens much too fast and encompasses all its branches. How does the Internet form the relationship between patients and medical staff? What information do patients seek and how do they get it? What problems arise during the communication process via new means? How can we describe an e-patient? How does the Internet model the doctor-patient relationship in case of cancer, one of the most dramatic diseases? Are students prepared to face an e-patient and how are they trained to do it? What is to be done to optimize internet communication between patients and health providers? This review analyzes information on these issues and outlines some opportunities for solving problems arising against the background of IT use in health care.